Dr. Johann Faust’s Transformations: from Faust to Faustianism - Arakelyan, Ara (Bulletin of Yerevan University B: Philology, 2021)
The article is dedicated to the study of one of the most famous monuments of world literature, the medieval German legend about Faust and the various literary works created around it.Since the publication the character of Faust has remained in the center of attention of the literary and scientific community. Over the centuries an extensive literature has been created on literary development, interpretation, imitation and reproductionbased on the text of legend. From era to era , the character erased from its medieval diaper, gets new lines and to some extent even returns to the original mythology.